RESPON PERTUMBUHAN TANAMAN SELADA (Lactuca Sativa L) TERHADAP VOLUME AIR DAN KONSENTRASI LARUTAN NUTRISI GOOD-PLANT SECARA HIDROPONIK - Nuryulsen Safridar; Sri Handayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2019)
This study aims to determine the volume of water and the concentration of the nutrient solution and the right good plant to plant growth of lettuce (lactuca sativa L). This research has been carried out in the garden experiment Jabal Ghafur Faculty of Agriculture, University of Sigli. Runs from February to April 2017. This study used a raft floating hydroponics system. Research using completely randomized design (CRD) factorial pattern that is factor of the volume of water and nutrient concentration factor of good-plant. Treatment of the water volume (V) consists of three levels ie (V1) 4 liters of water, (V2) 8 liters of water and (V3) 12 liters of water. Good treatment-plant nutrient concentrations (N) consists of three levels ie (N1) 600 ppm (N2) of 800 ppm and (N3) 1000 ppm, with three replications so overall deplore 27 experimental unit. The volume of water very significant effect on plant height and leaf length aged 10, 20 and 30 days after planting, leaf number aged 20 and 30 days after planting, heavy wet stover age 30 HST, significantly affect the amount of leaf age 10 HST. Good-plant nutrients very significant effect on plant height ages of 20 and 30 days after planting, leaf number and length of leaf age 30 HST, significant effect on plant height HST age 10, age 20 HST leaf length, weight of wet age 30 HST stover. Keywords: lettuce, hydroponics, water volume and concentration of good-plant nutrients